Large extracellular vesicles (microvesicles) in diabetic nephropathy: a systematic review of preclinical studies - Ghanem, Sarah Khalaf; Abdelsalam, Shahenda Salah; Bader, Loulia; Agouni, Abdelali (Frontiers in Pharmacology, 2025)
Diabetic nephropathy (DN) is a significant complication of diabetes and is characterized by progressive kidney damage and dysfunction. Several studies have highlighted the role of a subset of large-sized extracellular vesicles (EVs), commonly known as microvesicles (MVs), as crucial mediators of DN pathophysiology. This systematic review critically evaluates the methodological approaches used to study MVs in experimental models of DN, while also synthesizing the experimental endpoints investigated, to identify consistencies, gaps, and opportunities for standardization. A systematic literature search across PubMed, Embase, and Scopus identified preclinical studies investigating the impact of MVs on renal injury, inflammation, and fibrosis in diabetes. Seven preclinical studies published between 2014 and 2022 met the inclusion criteria. Data extracted: MV origin, isolation/characterization/quantification, models/conditions, dosing/exposure, and endpoints. Seven studies (2014–2022) met criteria. Differential centrifugation predominated for isolation; flow cytometry (FCM) (often Annexin V ± lineage markers), nanoparticle tracking analysis (NTA), and electron microscopy (EM) variably supported identity/size; FCM and NTA were commonly used for enumeration along with protein assays. MV sources included platelets, podocytes, urinary fractions, and MSC-derived vesicles. Across studies, MVs modulated oxidative stress (NOX4/ROS), inflammation (e.g., TNF-α, CXCL7), fibrotic signaling (p38 MAPK/CD36), and cell injury; cargo (e.g., miR-451a) linked to cell-cycle regulators (p15/p19) in early DN. Notable heterogeneity in media depletion, dose reporting, and detection thresholds limited cross-study comparison. We conclude that preclinical evidence supports MVs as early biomarkers and mechanistic drivers in DN, but standardization in isolation, characterization, dosing, and endpoint panels—aligned with MISEV 2023—is needed to enable comparability and translation.